Penyuluhan terpadu dalam mencegah stunting terkait kesehatan reproduksi remaja dan MPASI - Utama, Feranita; Rini Anggraini; Aerosta, Danny Kusuma; Sitorus, Rico Januar; Ermi, Nurmalia; Najmah, Najmah (Fakultas Kedokteran Universitas Sriwijaya, 2024)
More than a third of toddlers in Indonesia are stunted and this condition can continue into their teens. The adverse effects of stunting on children can be in the short term, such as growth and development disorders, low immune system and leading to mortality, while long-term impacts, such as short stature in adulthood, low school performance and work productivity, and low reproductive health. Pregnancy in adolescents and inadequate of complementary foods for toddlers has also contributed to the increasing prevalence of stunting. Increasing adolescent knowledge about reproductive health-risk of teenage pregnancies and mothers' knowledge about healthy complementary foods will prevent pregnancy in adolescents and stunting in toddlers. This integrated socialization for adolescents who junior high school students in SMPN 4 Indralaya Utara and mothers in Soak Batok Village is expected to support the program to reduction of stunting in Soak Batok Village, Regency of Ogan Ilir. The results of the evaluation showed that socialization for adolescents increased their knowledge about reproductive health and socialization for mothers of Soak Batok Village was enthusiastically received by them.